Physical Modeling in MATLAB - Downey, Allen (Open textbook library., 2021)
Modeling and simulation are powerful tools for explaining the world, making predictions, designing things that work, and making them work better. Learning to use these tools can be difficult; this book is my attempt to make the experience as enjoyable and productive as possible. By reading this book — and working on the exercises — you will learn some programming, some modeling, and some simulation: With basic programming skills, you can create models for a wide range of physical systems. My goal is to help you develop these skills in a way you can apply immediately to real-world problems. This book presents the entire modeling process, including model selection, analysis, simulation, and validation. I explain this process in Chapter 1, and there are examples throughout the book. Simulation is an approach to modeling that uses computer programs to implement models and generate predictions. This book shows how simulations are used to run experiments, answer questions, and guide decision-making.